2020
DOI: 10.1161/circimaging.120.011199
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Psoriasis With Biologic Therapy Is Associated With Improvement of Coronary Artery Plaque Lipid-Rich Necrotic Core

Abstract: Background: Lipid-rich necrotic core (LRNC), a high-risk coronary plaque feature assessed by coronary computed tomography angiography, is associated with increased risk of future cardiovascular events in patients with subclinical, nonobstructive coronary artery disease. Psoriasis is a chronic inflammatory condition that is associated with increased prevalence of high-risk coronary plaque and risk of cardiovascular events. This study characterized LRNC in psoriasis and how LRNC modulates in response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 33 publications
2
54
0
1
Order By: Relevance
“…Carotid plaques were assessed in pre-operative CT angiographies using a semi-automated, histology-validated software as previously described (The vascuCAP ® (Elucid Bioimaging Inc., Boston, MA, USA) software) [ 36 , 37 , 38 , 39 , 40 , 41 ]. In brief, reconstructed images were analyzed in a blinded fashion by one observer (EK) to characterize plaque structure and composition (plaque morphology) [ 4 ] creating 3D segmentations with improved resolution and soft tissue plaque component differentiation.…”
Section: Methodsmentioning
confidence: 99%
“…Carotid plaques were assessed in pre-operative CT angiographies using a semi-automated, histology-validated software as previously described (The vascuCAP ® (Elucid Bioimaging Inc., Boston, MA, USA) software) [ 36 , 37 , 38 , 39 , 40 , 41 ]. In brief, reconstructed images were analyzed in a blinded fashion by one observer (EK) to characterize plaque structure and composition (plaque morphology) [ 4 ] creating 3D segmentations with improved resolution and soft tissue plaque component differentiation.…”
Section: Methodsmentioning
confidence: 99%
“…However, significantly, these changes were transient and were not present at 52 weeks of therapy [ 72 ]. Biologic therapy for psoriasis has also been proved to have a beneficial influence on the modification of the lipid-rich necrotic core, which is a high-risk coronary plaque feature [ 73 ].…”
Section: The Influence Of Systemic Antipsoriatic Agents On Lipidemiamentioning
confidence: 99%
“…Colchicine is another anti-inflammatory drug that may result in plaque stabilization, 95 reducing the incidence of noncardioembolic ischemic stroke in patients with stable coronary artery disease. 96 Promising imaging-based studies have shown the impact of anti-inflammatory therapy on plaque progression and composition in the coronary arteries, 97 suggesting similar effects and ability to assess them in the carotid arteries as addressed by this roadmap.…”
Section: Updated Drug Therapy: Evidence and Impactmentioning
confidence: 96%